Synergistic Antiproliferative Effects of Co-nanoencapsulated Curcumin and Chrysin on MDA-MB-231 Breast Cancer Cells Through Upregulating miR-132 and miR-502c. (3rd October 2019) - Javan, Naser; Khadem Ansari, Mohammad Hassan; Dadashpour, Mehdi; Khojastehfard, Mehran; Bastami, Milad; Rahmati-Yamchi, Mohammad; Zarghami, Nosratollah
Abstract: In this study, we explored whether co-nanoencapsulated Curcumin (Cur) and Chrysin (Chr), natural herbal compounds with antitumor activities, regulate miR-132 and miR-502c and their downstream targets, leading to the synergistic growth inhibition in MDA-MB-231 breast cancer cells. For this purpose, Cur and Chr were co-encapsulated into PLGA-PEG nanoparticles (NPs) and characterized through DLS, FTIR and FE-SEM. MTT assay and cell cycle arrest analysis revealed that CurChr-loaded NPs had a considerable synergistic cytotoxicity against MDA-MB-231 cells with more cell accumulation in G2/M phase compared to the other groups. In addition, highest percentage of cell apoptosis was acquired in cells treated with CurChr-loaded NPs according to apoptosis analysis. Real-time PCR findings revealed that co-encapsulated form of Cur and Chr than free combination could further upregulate miR-132 and miR-502c expression ( P  < 0.001). Also, the strong reduction was detected in the protein levels of HN1 and P65 at the cells co-nanodelivered with Cur and Chr. These findings demonstrated that the co-nanodelivery of Cur and Chr through targeting miR-132 and miR-205c might be a novel strategy for the treatment of breast cancer.